Evidence of plaggen soils in SW Norway. Issue 4 (3rd July 2014) - Schnepel, Carolin; Potthoff, Kerstin; Eiter, Sebastian; Giani, Luise
Abstract This study aimed at clarifying whether a notable group of soils of the Jæren region, SW Norway, with deep humus‐rich top soils support a man‐made genesis. Four sites were investigated. The soils are characterized by thick top soils of 45, 70, 80, and 90 cm, which are enriched in soil organic matter and often also in artifacts, like fragments of potter's clay, indicating an anthropogenic origin. Soil pH ranges from 5.4 to 6.2 (H2O) and 4.4 to 5.3 (CaCl2), respectively. Soil organic C (SOC) contents range from 6.4 to 51.6 g kg−1 and N contents vary between 0 and 2.9 g kg−1. Increased P contents of up to 2, 924.3 mg kg−1 total P (Pt) and 1, 166.4 mg kg−1 citric acid‐soluble phosphorus (Pc) in the humus‐rich top soils support the assumption of an anthropogenic influence. Although many characteristics indicate an anthropogenic genesis, one soil lacks the required depth of 50 cm of a plaggen horizon and cannot be classified as Plaggic Anthrosol (WRB) and Plagganthrept (US Soil Taxonomy). As the requirement is 40 cm in the German system, all soils can be classified as Plaggenesch. The formation of these soils is related to human activity aiming at increasing soil fertility and overcoming the need of bedding material, the basic aims of the plaggen management in Europe. Highest P contents ever found for this kind of soils and references from the literature indicate that the formation of the soils in Norway started at Viking time, hence, being older than most other Plaggic Anthrosols.